Pemeriksaan Kadar Glukosa, Asam Urat Dan Kolesterol STIKes Salewangang Maros - Syafruddin, Syafruddin; Djunaedi, Djunaedi; Intang, Sitti Nur; Selvia, Selvia; Vitariani, Aisyah; Astuti, Fanni (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The Ministry of Health stated that non-communicable diseases cause high death rates every year and can affect individuals of various ages and countries throughout the world. Non-communicable diseases include heart disease, diabetes mellitus and diseases of kidney function. To overcome these health problems, preventive measures are needed that aim to improve the nation's quality of life. This is stated in the Presidential Instruction which is part of the meaning of Germas, namely regular health checks which are useful for facilitating early detection of diseases or health problems. The examinations carried out are divided into 2, namely laboratory examinations (blood examination, blood sugar levels, fat levels, kidney function/uric acid, liver function, and electrolytes) and physical examinations (ECG, etc.). The aim of community service is to provide an overview of current blood sugar levels, uric acid, cholesterol levels and body flexibility in the spine for Lecturers and Staff of Stikes Salewangan Maros and community members around the campus. The method involves checking blood sugar levels, uric acid and cholesterol as well as assessing body flexibility. The results obtained were that 60 (98%) respondents had normal blood sugar levels, 39 (64%) respondents had normal uric acid levels, 32 (52.5%) had cholesterol < 200 mg/dl, and 51 (83%) .6 %) shows excellent flexibility. Conclusion. Most of the respondents had normal blood sugar levels, uric acid levels, cholesterol levels and the majority of respondents showed excellent flexibility.